Effects of ChondroT on potassium Oxonate-induced Hyperuricemic mice: downregulation of xanthine oxidase and urate transporter 1 - Oh, Dool-Ri (BMC Complement Altern Med, 2019)
BACKGROUND: ChondroT, a new herbal medication, consists of the water extracts of Osterici Radix, Lonicerae Folium, Angelicae Gigantis Radix, Clematidis Radix, and Phellodendri Cortex (6:4:4:4:3). We previously reported that ChondroT showed significant anti-arthritis and anti-inflammatory effects. METHODS: This study was designed to evaluate the effect of ChondroT on hyperuricemia. First, the effect of ChondroT was evaluated on xanthine oxidase (XOD) activity in vitro. The anti-hyperuricemic effect of ChondroT was also studied in potassium oxonate (PO)-induced hyperuricemic model mice. Uric acid (UA) and XOD were evaluated in the serum, urine, and liver of the mice. In addition, we measured serum creatinine (Cr) and blood urea nitrogen (BUN) levels as well as mRNA expression of the mouse urate transporter 1 (mURAT1) to evaluate kidney function and urate excretion in hyperuricemic mice. RESULTS: ChondroT showed in vitro XOD inhibitory activity in a dose-dependent manner (P < 0.05). We demonstrated that ChondroT (37.5, 75 and 150 mg/kg) significantly reduced serum UA (P < 0.01 and P < 0.001, respectively), and upregulated urinary UA (P < 0.001, respectively) in PO-induced hyperuricemic mice. In addition, ChondroT (75 and 150 mg/kg) significantly reduced Cr (P < 0.05 and P < 0.01, respectively), BUN (P < 0.05 and P < 0.001, respectively), GOT (P < 0.05 and P < 0.01, respectively), and GPT (P > 0.05 and P < 0.05, respectively) levels in PO-induced hyperuricemic mice. ChondroT (75 and 150 mg/kg) also significantly downregulated serum (P < 0.05) and liver (P < 0.05) XOD activity. Compared to the hyperuricemic mice, the ChondroT (37.5, 75, and 150 mg/kg)-treated mice showed decreased mURAT1 protein expression level. CONCLUSION: ChondroT displayed anti-hyperuricemic effects by regulating XOD activity and kidney mURAT1.